2022
DOI: 10.1155/2022/7129610
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Automatic Water Spraying System for Solar Photovoltaic Module

Abstract: Photovoltaic (PV) cell has a characteristic of decrease in power beyond a certain temperature. This decrease in power is due to a drop in the open circuit cell voltage. This decreases the efficiency of the PV cell. The objective of this research is to increase the efficiency of PV cells by reducing the PV cell temperature and reflection loss. The cell temperature and reflection loss can be reduced by spraying water over the PV cells. On spraying water over the USP36, 24V PV module, the power is found to be inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Used, heated water may be then used for domestic purposes. The daily usage of water on the panel heated to more than 45 • C amounts to 15.6 L. Maximum cooling allowed a temperature drop of 20 • C, and the average drops were approximately 10 • C [78]. A different approach is presented by a team of scientists from the Institute of Science and Technology in Henan, China and two Egyptian universities.…”
Section: Discussionmentioning
confidence: 99%
“…Used, heated water may be then used for domestic purposes. The daily usage of water on the panel heated to more than 45 • C amounts to 15.6 L. Maximum cooling allowed a temperature drop of 20 • C, and the average drops were approximately 10 • C [78]. A different approach is presented by a team of scientists from the Institute of Science and Technology in Henan, China and two Egyptian universities.…”
Section: Discussionmentioning
confidence: 99%
“…Research with the aim of increasing the efficiency of PV modules by lowering their temperature and decreasing the reflection loss of irradiance was also carried out by Kumar et al [19]. It was found that the power of a PV panel increased when it was splashed with water.…”
Section: Cooling Of Pv Panelsmentioning
confidence: 99%
“…This reduces the efficiency of the solar panels and can even cause damage to them [5]. There are various ways of cooling solar panels or/and using this heat [6][7][8], but the most promising way is to create hybrid photovoltaicthermoelectric devices, in which this heat is directly converted into electricity [9][10][11][12][13]. This explains the increasing attention of researchers to materials possessing thermoelectric and photovoltaic properties simultaneously.…”
Section: Introductionmentioning
confidence: 99%